(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The CoViD-19 health emergency severely stressed the interdependence model between center and periphery, which characterizes the Italian constitutional order. The need of applying contrast measures, common to the whole national territory, did not prevent tensions and conflicts between the central State and the Regions, bringing out the necessity to find tools useful for reconnecting peripheral entities with central determinations. The article analyzes the connection tool of this crisis, built on a peculiar connection between a covering law decree, guarantee of the legal reserve imposed by the Constitution for the limitation of some fundamental rights, and the decrees of the President of the Council of ministers, issued only after hearing the peripheral organisms. A model that seems to have worked.